Pengaruh Kepemimpinan, Kompensasi dan Displin Kerja Terhadap Kinerja Karyawan Pada Hotel Cendana Resort & Spa Ubud, Gianyar - Ariana, I Wayan Tresna; Riana, I Gede (E-Jurnal Manajemen, 2013)
The development on the hospitality industry businesses in Bali, especially in the Ubud, today felt more advanced and rapid impact and very competitive. Until now in the Ubud there are many 3-star hotel. Hotel Cendana Resort & SPA is one of the hospitality business in Ubud, Gianyar. As one of 3-star hotel that exist in ubud, of course, the quality of service achieved based on good  employee's performance. Therefore companies need to pay attention to the factors that have affect towards performance factors such as leadership, compensation and work discipline. The purpose of this study was to find out the effect between leadership, compensation, and discipline towards employee performance in simultaneously and partially in the Hotel Cendana Ubud Resort & SPA, Gianyar. By using saturated sampling technique has been obtained number of sample were 51 respondents. Data analysis techniques by using multiple linear regression. The results has been obtained that are there are significant effects in simultaneously and partially between leadership, compensation, and discipline towards the employee’s performance in the Hotel Cendana Ubud Resort & SPA. Keywords: Leadership, Compensation, Labor discipline, Performance